The Global Age: An Application to Societal Change in Muslim Societies - Al-Roubale, Amer (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Global Age: An Application to Societal Change in Muslim Societies